Ageing and Technology : Perspectives From the Social Sciences - Emma Domínguez Rué; Linda Nierling (transcript, 2016)
The booming increase of the senior population has become a social phenomenon and a challenge to our societies, and technological advances have undoubtedly contributed to improve the lives of elderly citizens in numerous aspects. In current debates on technology, however, the »human factor« is often largely ignored. The ageing individual is rather seen as a malfunctioning machine whose deficiencies must be diagnosed or as a set of limitations to be overcome by means of technological devices.This volume aims at focusing on the perspective of human beings deriving from the development and use of technology: this change of perspective – taking the human being and not technology first – may help us to become more sensitive to the ambivalences involved in the interaction between humans and technology, as well as to adapt technologies to the people that created the need for its existence, thus contributing to improve the quality of life of senior citizens.